Pengaruh Brand Loyalty, Brand Image Dan Harga Terhadap Keputusan Pembelian Kosmetik Wardah Di Kota Yogyakarta - Liyamilati Hanifah; Heri Prasetyo (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
The Influence of Brand Loyalty, Brand Image and Price on Wardah Cosmetics Purchasing Decisions among Female Students in the City of Yogyakarta. This research aims to determine the influence of brand loyalty, brand image and price on purchasing decisions for Wardah cosmetics among female students in the city of Yogyakarta. Using descriptive quantitative research methods, determining the sample using the Lemeshow formula with 100 respondents, sampling using purposive sampling technique with the following criteria: 1) Active students in the city of Yogyakarta who use Wardah cosmetics, 2) Have purchased Wardah cosmetics at least once. Data collection techniques using a Questionnaire which then processed the data using IBM SPSS 25. The results of this research are that Brand Loyalty has a t-test calculated value of 6,372, a Brand Image t-test calculated value of 2,297 and a Price t-test calculated value of 5,958. This means that the independent variables Brand Loyalty, Brand Image and Price partially have a positive and significant effect on purchasing decisions. The F-test value is 117,049. This means that the variables Brand Loyalty, Brand Image and Price simultaneously have a positive and significant effect on purchasing decisions.